2018
DOI: 10.1103/physrevlett.120.214501
|View full text |Cite
|
Sign up to set email alerts
|

Flow Topology Transition via Global Bifurcation in Thermally Driven Turbulence

Abstract: We report an experimental observation of a flow topology transition via global bifurcation in a turbulent Rayleigh-Bénard convection. This transition corresponds to a spontaneous symmetry breaking with the flow becomes more turbulent. Simultaneous measurements of the large-scale flow (LSF) structure and the heat transport show that the LSF bifurcates from a high heat transport efficiency quadrupole state to a less symmetric dipole state with a lower heat transport efficiency. In the transition zone, the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
6
26
0
Order By: Relevance
“…When a swirl is present, it can act as a source of toroidal vorticity (i.e., the vorticity associated with the poloidal movement), as can be checked by taking the curl of Eqs. (1) and (2). The vorticity is thus not conserved anymore, making the dynamics intermediate between 2D and 3D.…”
Section: Axisymmetric Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…When a swirl is present, it can act as a source of toroidal vorticity (i.e., the vorticity associated with the poloidal movement), as can be checked by taking the curl of Eqs. (1) and (2). The vorticity is thus not conserved anymore, making the dynamics intermediate between 2D and 3D.…”
Section: Axisymmetric Turbulencementioning
confidence: 99%
“…are gradually or abruptly broken, when increasing the Reynolds number. More recently, transitions between different turbulent states with different statistical symmetries were evidenced either experimentally [1,2] or numerically [3,4], still falling into the classical paradigm of spontaneous symmetry breaking.…”
Section: Introductionmentioning
confidence: 99%
“…Several findings have suggested that wall-bounded turbulent flows can take different statistically stationary turbulent states, with different length scale of the flow structures and with different transport properties, even for the very same values of the control parameters. Examples for the coexistence of such multiple turbulent states include turbulent (rotating) Rayleigh-Bénard convection [2][3][4][5][6][7][8], Taylor-Couette turbulence [9][10][11], double-diffusive convection turbulence [12], von Karman flow [13][14][15][16], rotating spherical Couette flow [17], Couette flow with span-wise rotation [18], but also geophysical flows [19,20] such as in ocean circulation [21][22][23], in the liquid metal core of Earth [24][25][26][27], or in the atmosphere [28,29].…”
mentioning
confidence: 99%
“…Tsinober 16 postulated that the enstrophy production is large in S4 topology whereas the strain rate production is concentrated in regions of S1 topology. The flow topology distributions in Rayleigh–Bénard convection, where temperature and velocity fields are intrinsically coupled, are yet to be analysed in detail 17 20 in comparison to the vast body of literature (e.g. Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses by Dabbagh et al 17 19 revealed the existence of the teardrop shape in the bulk region away from the walls in Rayleigh–Bénard convection but the small scale structures in the vicinity of the hot and cold walls have not been discussed there in terms of Q and R . Xi et al 20 reported a transition of flow topologies from a quadruple structure to a dipole structure based on Rayleigh number in turbulent Rayleigh–Bénard convection, which has implications on the Nusselt number (or heat transfer rate). A recent analysis revealed that large-scale circulation in Rayleigh–Bénard convection is affected by Prandtl number 21 .…”
Section: Introductionmentioning
confidence: 99%